A diatom-based palaeosalinity history of Ace Lake, Vestfold Hills, Antarctica - D Roberts; Andrew McMinn (1999)
A comprehensive diatom stratigraphy is used to calculate a palaeosalinity history for an Antarctic lake via an established diatom-salinity transfer function for the Vestfold Hills, Antarctica. A sediment core taken from Ace Lake in 1995 shows three distinct changes in diatom assemblage constituents: initial benthic hyposaline - freshwater taxa are replaced by marine planktonic and sea-ice taxa with these taxa in turn replaced by the benthic hypersaline taxa dominant in the lake today. These changes in assemblage composition enable the lakewater salinity of each stage to be determined, and the Holocene evolution of the lake to be refined. Deglaciation of the Vestfold Hills at the beginning of the Holocene exposed Ace Lake basin; following this, fresh lacustrine diatoms were deposited from ~11 380 to ~8110 corrected 14C yr BP. Relative sea-level rise after this time led to the progressive marine inundation of the lake and the deposition of marine diatom taxa. Marine taxa were dominant in the sediment for more than 6000 years. Isostatic rebound and stabilization of the sea-level isolated Ace Lake and at ~1480 corrected 14C yr BP saline lacustrine diatoms became the dominant taxa, indicative of the concentration of dissolved salts through evaporation after isolation.